Physical performance discriminating winning and losing in UEFA Champions League: a full-season study - Modric, Toni; Versic, Sime; Jukic, Igor; Sekulic, Damir (Biology of Sport, 2025)
This study aimed to examine the differences in physical performance when winning and losing in UEFA Champions League (UCL) matches. Data were collected using an optical tracking system from all UCL matches ( n = 125) in the 2022/23 season. A linear mixed model was used to examine the differences in physical performance in won and lost matches while controlling for match location, team formation, opponent quality, playing time, red cards, and between-player, -team, and -match variations. The results indicated that (i) wingers and forwards covered ~ 20% greater high-intensity running distance in won compared to lost matches (Cohen’s d (d) = 0.76 and 0.96, respectively), (ii) central defenders and fullbacks covered ~ 15% greater high-intensity running distance in lost compared to won matches ( d = 0.59 and 0.32, respectively), (iii) offensive midfielders achieved ~ 2% greater low-intensity running distance ( d = 0.59) while defensive midfielders performed ~ 2% greater total distance ( d = 0.81) in won compared to lost matches. These findings suggest that winning was physically more demanding for offensive players but losing was more demanding for defensive players, while midfield players’ physical demands were similar irrespective of winning and losing. Soccer coaches should consider implementing an extended period of recovery for offensive and defensive players following won and lost matches, respectively.